Low Cost Boundary Scan Controller for Didactic Applications (IEEE 1149.1) - Fidalgo, André Vaz (2015)
The Boundary Scan (BS) technology is widely used in the testing and debugging of Printed Circuit Boards (PCBs), being employed in various phases of product manufacturing and contributing to a very pronounced cost reduction when compared to alternative test techniques. Also, the BS technology is frequently used as a pedagogical tool. This technology is presented on a "Debug and Test of Electronic Systems" course, and up until now the students experience relied on empirical analysis and simulators. The idea behind the proposed solution was the development of a remotely accessible lab that allows the practical use of the technology using real digital circuits and an accessible and pedagogical test environment. This paper describes the design and development of a working prototype, the implemented hardware and software and the proposed integration into the pedagogical environment. Although implemented remote access capabilities are still limited, this is a work in development, which has considerable progress margin and the potential to become a commercial-level product.